Coping With Technology In Academic Libraries - Saupi Udin, Zanaria (2015)
Technology has provided tremendous improvements to library services. The transfer of digital information to meet all the requirements for preservation, distribution and manipulation of knowledge are significantly faster today. Radical changes are occurring in digitizing collections, preserving digital archives and improving data storage and retrieval methods. The emergence of a digital lifestyle has challenged the traditional role, vision, purpose and operation of libraries. The transition from automation to digitization meant that librarians had to acquire new skills and competencies and be educated in the new technologies, which in turn added a further burden and stress to them. Due to this transformation and the lack of formal technical qulification among librarians, it is not highly surprising that many find their job responsibilities demanding and strenuous. This paper serves as a preliminary background into the nature of librarians who are supporting library operations through the application of technologies in academic libraries. The focus is on systems librarians because they are in a better position to see issues that relate to the overall implementation and management of technological resources within the organisation. The study then discusses several strategies to cope with technologies based on a study conducted by Nicole Engard and Rachel Gordon (2012)